INSTITUTIONS AND TECHNOLOGY DIFFUSION IN AGRICULTURE: ROLE OF ISRO VILLAGE RESOURCE CENTERS - C S, Shaijumon (European Scientific Journal, ESJ, 2014)
Economic development and growth requires institutional frameworkthat allows economic actions to take place in an orderly and focused manner.Technology allows the rural people to get more access to knowledge andresources and that will help them to gain more economic benefits. Successfultechnology/knowledge transfers from lab to land improve efficiency ofproduction, and transform the economy to a more productive one. However,the potential benefits of technology are realized only when it is successfullytransferred to a large number of end-users. Space technologies are state ofthe art technologies of modern civilization. Indian Space ResearchOrganization (ISRO), with the intention of disseminating knowledge to ruralmasses has envisaged the Village Resource Centre (VRC) concept in 2004.ISRO‘s VRC conduct interactive programmes on a regular basis and areconnected to knowledge producing institutions and agencies. This studyempirically analyzes the impact of VRCs in agriculture by capturingproductivity, level of knowledge and innovation performances. Results showthat the impact of new developmental intervention through Village ResourceCenters are significant in knowledge diffusion, innovativeness, andproductivity of farming communities, and are quantitatively measured. Thereis a significant reduction of information inequality and noticed theemergence of a new socio-economic relationship. VRC‘s helps in improvingthe quality of life in villages by providing new knowledge. The services arereaching the doorsteps of common man, in local language.